Paper Memories, Presented Selves: Original Order and the Arrangement of the Donald G. Simpson Fonds at York University - Harris, Carolyn (Archivaria, 2012)
As the acquisition of modern, recently created records has become more common, new challenges and opportunities have become part of archivists’ work. Original order in contemporary, open personal fonds is no longer the tidy concept introduced by Muller, Feith, and Fruin, but more often a moving target, and arrangement is much less self-evident or simple than in former days. This article is a case study about archival arrangement, order, the experience of working with a living donor, and particularly the intellectual struggle between theory and practice encountered by the author during the arrangement and description of the Donald G. Simpson Fonds at the Clara Thomas Archives and Special Collections at York University in Toronto. The article discusses and reflects upon the ways in which original order was interpreted given that the received order was a self-conscious construction of the creator, making archival arrangement an interesting endeavour to protect evidential value while revealing the fonds’ immense informational value to users. The Simpson Fonds is an intriguing, real-world example that supports recent reconceptions of original order in the archives literature. In discussing Simpson’s (re)arrangement, the author references critical theory on life writing and its ideas about identity, self-representation, and memory in order to draw parallels between the processes of writing the self and documenting the self. The author also explores the benefits, opportunities, and challenges that came with having a “live” donor. This is a unique case of participatory archiving with an enthusiastic and active donor. It contributes to the sparse archives literature on working with personal records, and shares one archivist’s experience interpreting original order as it manifested in this personal fonds. RÉSUMÉ À mesure que l’acquisition de documents d’archives modernes et nouvellement créés est devenue plus courante, le travail des archivistes s’est ouvert à de nouveaux défis et à de nouvelles opportunités. L’ordre original pour les fonds personnels ouverts et contemporains n’est plus le concept clair et précis que Muller, Feith et Fruin ont introduit; c’est plus une cible mouvante et le classement est beaucoup moins évident et simple que dans le passé. Cet article présente une étude de cas au sujet du classement archivistique, de l’ordre, de l’expérience de travail avec un donateur vivant, et en particulier, du débat intellectuel entre la théorie et la pratique que l’auteure a connue lorsqu’elle traitait et décrivait le fonds Donald G. Simpson aux Clara Thomas Archives and Special Collections à Université York à Toronto. L’auteure examine et réfléchit aux façons dont l’ordre original a été interprété, puisque l’ordre établi était une construction volontaire du créateur, ce qui a fait du traitement de ce fonds une entreprise intéressante pour protéger la valeur de preuve tout en mettant l’accent pour les chercheurs sur l’immense valeur informationnelle du fonds. Le fonds Simpson est un exemple réel et intrigant qui appuie les récentes redéfinitions de l’ordre original rencontrées dans les écrits en archivistique. En examinant le (re)classement du fonds Simpson, l’auteure fait référence à la théorie critique sur l’écriture biographique et à ses idées autour de l’identité, de la représentation de soi et de la mémoire, dans le but d’établir des parallèles entre les processus d’écrire au sujet de soi et de laisser de traces écrites de sa vie. L’auteure explore les avantages, les opportunités et les défis encourus lorsqu’on travaille avec un donateur vivant. Il s’agit d’un cas unique d’archivage participatif avec un donateur enthousiaste et actif. Cet article contribue au très petit corpus de documents savants portant sur les archives personnelles et il partage les expériences d’une archiviste qui interprète l’ordre original tel qu’il s’est manifesté dans ce fonds personnel.